Simplified exercise test for the initial differential diagnosis of Pneumocystis carinii pneumonia in HIV antibody positive patients. Issue 2 (February 1994) - Sauleda, J; Gea, J; Aran, X; Aguar, M C; Orozco-Levi, M; Broquetas, J M
Abstract : BACKGROUND--This study was designed to evaluate the usefulness of a simplified exercise test in the differential diagnosis of Pneumocystis carinii pneumonia (PCP). METHODS--Forty five subjects with antibodies against the human immunodeficiency virus (HIV) and pneumonia were included and divided into two groups: those with PCP and those with "other pneumonias" (non-PCP). The test involved pedalling for two minutes on a stretcher bed and was considered positive if SaO2 decreased by at least 3%. RESULTS--During the exercise the mean(SE) SaO2 fell in patients with PCP from 88(4)% to 84(3)%, p < 0.01, whilst it improved slightly in subjects with non-PCP from 91(1)% to 93(3)%, p < 0.05. Sensitivity was 77% and specificity 91%. CONCLUSIONS--This simple test seems potentially useful for the initial investigation of HIV antibody positive patients with pneumonia.